The hydrocyclone - Bradley, Douglas (International series of monographs on chemical engineering, 1965)
Providing a comprehensive review of all the aspects of the theory, design, performance, and application of hydrocyclone, this book provides a basis for further research, data for design, and an understanding of the hydrocylcone which will permit a wider applicaiton in industry. Special apsects include reviews of all available velocity distribution data ; of all of the important correlations of perfromance, both theoretical and empirical, of commericial equipment of the cyclone type. A review of British patents is included, and the comprehensive bibliography cites nearly 600 references. In view of the extreme lack of comprehensive review literature on the subject, and the comprehensive nature of this book, it will provide a valuable work of reference for research workers in universities and in industry. Graduate courses in chemical engineering and mining engineering include lectures on this subject and therefore the book constitutes recommended reading for students of such courses.